Hazard classification of active faults in Yunnan base on probabilistic seismic hazard assessment - Zhou Qingyun; Tian Peng; Liu Changwei; Liu Jingnan; Luo Weidong (Open Geosciences)
During a major earthquake, the hazard of active faults mainly manifests in two main aspects: seism enhancement near the fault (near-fault effect) and surface displacement. Since not all active faults will generate surface displacement, the hazard levels of active faults should be classified to achieve “scientific management of earthquake hazard.” Although previous classification methods have distinguished the hazard of active faults to some extent, these classification methods are often not based on the standard of “whether surface displacement will occur.” Therefore, these classification methods cannot be applied to avoid active faults. Based on the probabilistic seismic hazard assessment method, the maximum potential earthquake on active faults under different exceedance probabilities is calculated. According to the magnitude of the maximum potential earthquake and the possibility of surface displacement caused by earthquakes of different magnitudes, a classification approach for active faults is proposed. The classification method indicates that for civil buildings, only a portion (T RP < 2.72 ka) of the surface displacement hazard of the Holocene faults needs to be considered. On this basis, the hazard levels of active faults in Yunnan Province, China, are classified. The division results reveal that nearly half of the Holocene active faults in Yunnan Province have a hazard level lower than level A. Therefore, buildings do not need to avoid these active faults.